La ciudad y las indias Buenos Aires (1744-1820) - Jacqueline, Sarmiento (Identidades rioplatenses, 2023)
The city and Indigenous women: Buenos Aires (1744-1820). This book addresses the presence of Indigenous women in the city of Buenos Aires between 1744 and 1820, focusing on their forms of social interaction and incorporation into urban life. The main objective is to raise the visibility of this group of urban Indigenous women and their specific living conditions. To this end, the article is centered on the observation and problematization of their ways of performing in society, on the forms of subjection to which they were exposed and on the strategies they were able to implement in response to them. In this sense, the author proposes to analyze these women from the intersection of various identity categories and the definition of their specific conditions; to characterize their presence in the city, both in the urban space as a whole, as well as in domestic groups and institutions.